Inventário do ciclo de vida (ICV) da produção de soja no Paraná - Reichel, Leandro De Souza (2012)
This study had the objective to elaborate an Life Cycle Inventory (LCV) of the soy in the Paraná, being entered the main entrances and exits in the agricultural phase of production of the soy. The Life Cycle Assessment of Product (ACV) consists of the accounting of all the environmental impacts that have place since the acquisition of the raw material, of the products previously manufactured, until the o impact of life end. It attempts to measure the energy level and determine the main raw materials used in the production process of the soybean crop. The study it points with respect to a trend of increase in the production of biodiesel, beyond presenting a view in relation to the current situation of the State of the Paraná as the bigger producer of soy in Brazil, main oilseed used in the manufacture of biodiesel. The Life Cycle Inventory elaborated allowed to evidence the amounts of the main micronutrients, materials auxiliary and consumption of diesel in the form of inputs during the preparation of the ground and the seeds for the productivity of a ton of soy grains, being that all the calculations had been carried through for harvest 2010/2011, that a production of 15,4 million tons in the Region of the Paraná registered. The exits had been verified in the forms of emissions for the ground, atmospheric emissions and liquid emissions. It is verified that during the agricultural phase of the soy, the anthropic effects are raised when compares the amount of inputs and energy used in the process and the level of emission for the half-environment, having arrived to enter emissions around 90% of the total of the entrance. The Life Cycle Inventory presented in the work collaborates as instrument for the evaluation of the real impacts that the culture of the soy in its phase of agriculturist has in the State of Paraná, beyond presenting the methodology of the Life Cycle Assessment as instrument of evaluation of impact of productive processes.